A comparative study of bacterial contamination between open heart surgery wards and neurosurgery wards - Atalah Hussin, Nadia (Tikrit Journal of Pharmaceutical Sciences, 2023)
The main source of the infectious agents of the nosocomial infections is the patients and healthcare workers themselves as well as the environment. It is possible to significantly reduce the nosocomial infections through effective infection prevention and control programs. This study aimed by focus light on the importance of following the standard protocols, assist healthcare workers to improve the quality of the care they deliver. Materials and methods: This study took tow surgical departments in the same hospital .The first department was neurosurgery department the second one was the open heart surgery department and compared between the two departments in term of bacterial contamination of the working personnel, the post operative patients and the environment. The bacteria were isolated and identified according to the standard methods. Antibiotic sensitivity testing carried out by Kirby-Bauer disc diffusion method. The result: The bacterial contamination of ICU neurosurgery department air, bed headsed sheets, and floors were as follow; 47 %, 82 %, and 96.7 % respectively; compared to 0% of that of open heart surgery. The bacterial contamination of the OT of neurosurgery air, floors, beds and bed sheets were 83.3%, 95% and 75% respectively compared to 0% for that of open heart surgery. For the nurses in the ICU of neurosurgery all the samples came positive for bacterial culture. While in open heart department bacterial culture came negative for the nurses. About 23% of the patients in neurosurgery department developed postoperative infection compared to 1% of that of open heart surgery. The most common isolated bacteria were Coagulase –ve Staphylococcus. Conclusion: The significant low infection rate in the open heart surgery department compared to the neurosurgery department is a direct reflection to the good managing of the department that make full assurance of complete disinfection and complete compliance with standard precautions to prevent infection.